Responses difference analysis of soil potential nitrification rates to Cu and sulfadiazine. Issue 1 (1st January 2019) - Liao, Qiang; Li, Mingzhu; Dong, Yuanpeng; Shao, Yifei; Liu, Xijuan; Hu, Xinxin; Li, Menghong; Liu, Aiju
ABSTRACT: To investigate responses difference of soil potential nitrification rates (PNR) to heavy metals and antibiotics, batch toxicity experiments of Cu and sulfadiazine (SDZ) were conducted in four typical soils which were collected from different locations of China. Toxic differences of Cu and SDZ to soil PNR were evaluated based on their values of EC20  and EC50  calculated with logistic model. It was found that soil nitrification was a good indicator of Cu contamination in soils except for paddy soil. For SDZ,  their ECX values were significantly higher than its concentration level (0.002 ~ 0.760 mg·kg -1 ) in soils. Thus, it was concluded that soil nitrification might be more sensitive to Cu than SDZ in field soil. The further Pearson correlation analysis indicated that the response of soil PNR to Cu and SDZ contamination were significantly related with soil PNR0  and pH.